Functional Impairment Predicts Outcome of Youth With Headache in the Emergency Department. (January 2020) - Hemberg, Jennifer L.; Pomeranz, Elaine S.; Rogers, Alexander J.; Lo, Sharon L.; Harrison, Lauren E.; Donohue, BS, Laura E.; Kullgren, Kristin A.
Headache is a common presenting complaint in emergency departments (EDs), with the goal of improving acute pain. However, youth with chronic headaches may demonstrate broad functional impairment in their lives due to headaches. Our objective was to determine if degree of functional impairment predicts ED course for patients with headache as part of a clinical protocol. One hundred and thirty-seven pediatric patients presenting to an ED with headache were included. Patients and parents were administered the Functional Disability Index (FDI) and ED charts were reviewed to evaluate outcomes. Higher child-reported FDI scores were associated with more medications, longer ED stay, and admission. High parent-proxy FDI score was associated with longer ED stay. Both pain score and parent-proxy FDI score were associated with imaging. The FDI was a more useful predictor of visit resources than pain score. FDI scores could be used to help anticipate patients who may require greater time and resources.